Process Simulation & Sensitvity Analysis of Cumene Production from an Integrated Alkylation and Transalkylation Reaction - Hilman Ali Hazmi (Universitas Muslim Indonesia, 2022)
Cumene is a very important petrochemical commodity, mainly to produce phenol and acetone. The overall growth rate for cumene capacity has been healthy, averaging slightly less than 3.5 % per year to reach 18 million metric tons per year in 2017. The purpose of this study is to generate a steady-state process simulation using ASPEN HYSYS version 10 to produce a small capacity of 10 ton/h of cumene with 99.99 wt % product purity. An alkylation reaction of benzene with propylene is carried out for producing cumene by using a zeolites catalyst as modeled by Badger technology. Transalkylation is also integrated into the system for eliminating unwanted products such as p-diisopropyl benzene. The proposed simulation flowsheet provides a good convergence overall result. The preliminary utility consumption obtained from the simulation consists of approximately 0.0418 kton/h of steam, 1.22 kton/h of cooling water, and 450 kW of electrical duty. Optimization is carried out in the simulation by conducting a sensitivity analysis study to find the optimum operating conditions of the alkylation reactor with a dimension of 1.3 m diameter and 4 m of length. The result shows that at an optimum value of B/P molar ratio of 7, reactant temperature of 170 oC, and reactant pressure of 3 MPa, the selectivity of cumene obtained is at a high value of 0.9446, while the percentage conversion of propylene to cumene obtained is at a high value of 99.99 %.